Flame impact resistant high borosilicate glass and preparation method thereof
By special treatment of nano-scale crquartz and alumina, as raw materials for high borosilicate glass, the problem of reduced transparency after flame impact is solved, the fire resistance limit and transparency of the glass are improved, and the visibility of fire rescue is ensured.
Patent Information
- Application Number
- CN202411726899.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The transparency of existing borosilicate fire-resistant glass decreases after the flame impact, affecting fire rescue operations.
The nano-scale crescent quartz is subjected to lanthanum nitrate treatment and freeze-drying treatment, and the iron-chromium lignin sulfonate-treated alumina is used as the raw material component of the glass, so as to improve the refractory limit and transparency of the glass.
It achieves the effect of flame impact on transparency while improving the fire resistance limit of glass, ensuring visibility of fire rescue.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to flame impact-resistant high borosilicate glass and a preparation method thereof, belonging to the field of high borosilicate glass preparation. Background Art
[0002] When a fire occurs in a building, the glass curtain wall becomes a path for the fire to spread due to the ventilation effect. Moreover, after the fire occurs, the curtain wall often reaches its fire resistance limit and falls down before people are evacuated, seriously affecting the evacuation process. The application of fire-resistant glass makes up for this defect.
[0003] Fireproof glass is a new type of building material. It can not only maintain its integrity in the prescribed fire resistance test, but also isolate the transfer of heat. When a fire occurs, it can effectively prevent the spread of flames and heat transfer, and limit the fire to a small area near the ignition point, thus playing a role in fire protection. According to the structure and type, fireproof glass can be divided into single-piece cesium potassium fireproof glass, single-piece high borosilicate fireproof glass, composite fireproof glass, infusion fireproof glass, etc.
[0004] Among them, composite fireproof glass and infused fireproof glass are composed of two layers of glass (three layers of glass can also be used for special needs), sealed with special flame-retardant strips on all sides, and infused with fireproof glue in the middle. After solidification, it becomes a transparent jelly and adheres to the glass. When exposed to high temperature, the transparent jelly-like fireproof glue layer in the middle of the glass will quickly harden to form an opaque fireproof insulation board. While preventing the spread of flames, it also prevents high temperature from being transmitted to the back of the fire. However, bubbles are prone to appear in the production process, resulting in poor transparency and affecting the aesthetics. In addition, it will quickly turn milky white under ultraviolet radiation and flames, losing the basic function of glass transparency, making it impossible to observe the fire situation, affecting the judgment of rescue operations.
[0005] High borosilicate fireproof glass is a newly developed borosilicate glass with high chemical stability, high temperature resistance and high transparency in recent years. It is a highly safe fully tempered non-insulating single-piece fireproof glass. This type of single-piece has a fire resistance limit far exceeding that of single-piece cesium potassium fireproof glass.
[0006] In order to improve the fireproof performance of high borosilicate fireproof glass, it is necessary to increase its load softening point, so the requirements for its raw materials are relatively high, and the selection of silicon source is particularly important. Its microstructure is required to be fine, uniform and dense, and the phase composition is well matched, especially the ratio of cristobalite and tridymite. The main crystal phase is tridymite with a network structure of spearhead twins interlaced with each other. The higher volume stability of tridymite is used to make the glass have a higher load softening point and structural strength. However, it was found in the experiment that too much tridymite will cause the glass to not break after a long period of flame impact, but the transparency of the glass will still decrease to a certain extent. Although it will not lead to a complete loss of transparency, it will still affect the rescue operations at the fire scene. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the defects of the prior art. By subjecting nano-scale cristobalite to two-step special treatment and nano-scale alumina to sodium iron chromium lignin sulfonate, both are used as raw material components of glass, so as to reduce the influence of flame impact on the decrease of glass transparency while improving the fire resistance limit of glass.
[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0009] A flame-impact-resistant high borosilicate glass, the raw materials of which include phosphotasysine, freeze-dried nano-cristobalite, boron oxide, aluminum oxide treated with sodium iron-chromium lignin sulfonate, sodium oxide, lithium oxide and titanium oxide, and the mass ratio of the raw material components is 600-700:250-300:110-130:65-85:10-14:9-11:24-30.
[0010] The following are further improvements to the above technical solution:
[0011] The silicon dioxide content of the phosphotquartz is 99.84wt% and the particle size is 73μm;
[0012] The particle size of the titanium oxide is 34 μm.
[0013] The freeze-dried nano-cristobalite preparation method comprises lanthanum nitrate treatment and freeze-drying;
[0014] The method for the lanthanum nitrate treatment is:
[0015] The nano-scale cristobalite and lanthanum nitrate solution are mixed evenly, and sent to a grinder, and the rotation speed of the grinder is controlled to be 1150-1250 r / min, and the grinding time is 20-30 min. After the grinding is completed, the mixture is washed with deionized water until the pH value is 6.6-6.8, and then dried to obtain nano-scale cristobalite treated with lanthanum nitrate;
[0016] The mass ratio of the nanoscale cristobalite to the lanthanum nitrate solution is 1:6.5-7.5;
[0017] The nanoscale cristobalite has a silicon dioxide content of 99.85 wt%, a particle size of 140 nm, and a density of 2.44 g / cm 3 ;
[0018] The concentration of the lanthanum nitrate solution is 7.0-8.0 wt %.
[0019] The freeze-drying method is:
[0020] The lanthanum nitrate treated nano-quartz is mixed with the oxalic acid solution, stirred at a speed of 100-150 r / min for 50-80 min, and after the stirring is completed, the cooling rate is controlled to be 1.5-2.5°C / min, and the temperature is cooled to -35 to -45°C, and then maintained for 230-260 min, and then the pressure is adjusted to 3-6 Pa, and sublimation drying is performed to obtain freeze-dried nano-quartz;
[0021] The mass ratio of the nano-cristobalite treated with lanthanum nitrate to the oxalic acid solution is 1:7.5-12.5;
[0022] The concentration of the oxalic acid solution is 0.4-0.75 mol / L.
[0023] The preparation method of the aluminum oxide treated with sodium ferrochrome lignin sulfonate is as follows:
[0024] The nano-alumina is mixed with deionized water, stirred to make it dispersed evenly, and an alumina dispersion is obtained, and then sodium iron chromium lignin sulfonate is added to the alumina dispersion, the speed is controlled to be 210-260r / min, and stirring is performed, and hydrogen peroxide is continuously added during the stirring process, and the adding time of hydrogen peroxide is controlled to be 8-15min. After the addition is completed, the temperature is controlled to be 60-65°C, the speed is adjusted to be 90-130r / min, and stirring is continued for 330-400min. After the stirring is completed, the pH is adjusted to 9.5-9.9, and the temperature and speed are maintained to continue stirring for 25-35min. After the stirring is completed, the product is filtered, washed, and dried to obtain sodium iron chromium lignin sulfonate treated alumina;
[0025] The mass ratio of the nano-alumina, deionized water, sodium iron-chromium lignin sulfonate, and hydrogen peroxide is 10-20:100-200:1.8-2.2:0.9-1.1;
[0026] The particle size of the nano-alumina is 50 nm;
[0027] The concentration of the hydrogen peroxide is 25-35wt%.
[0028] The preparation method of the high borosilicate glass is:
[0029] The specified mass of phosphotyrite, freeze-dried nano-cristobalite, boron oxide, alumina treated with sodium iron-chromium lignin sulfonate, sodium oxide, lithium oxide and titanium oxide in the raw material components are mixed evenly, placed in a platinum crucible, and melted at a temperature of 1510-1550° C. After all the components are completely melted, the temperature is raised to 1620-1670° C. to obtain glass liquid, and the glass liquid is passed through a tin bath, and the molding temperature in the tin bath is controlled to be 825-875° C., and the outlet temperature of the tin bath is controlled to be 610-620° C., and float molding is performed, and the glass liquid is taken out of the tin bath after molding, and then annealed to obtain a high borosilicate glass resistant to flame impact.
[0030] Compared with the prior art, the present invention achieves the following beneficial effects:
[0031] The high borosilicate glass of the present invention has relatively excellent mechanical properties. According to the method in T / ZBH009-2019, the bending strength of the glass is tested, and the bending strength is 212-218 MPa; according to the method in GB / T37780-2019, the elastic modulus and shear modulus of the high borosilicate glass are detected, and the elastic modulus is 71-72 GPa, and the shear modulus is 4.32-4.41 GPa; according to the method in T / ZBH009-2019, the shotgun bag impact performance of the glass is tested, and the highest height at which the shotgun bag falls without being damaged is used as a test index, and the height is 2700-2800 mm; according to the method in GB15763.2-2005, the surface stress of the high borosilicate glass is detected, and the surface stress is 127-134 MPa;
[0032] The high borosilicate glass of the present invention has relatively excellent fire resistance and heat resistance. According to the method in T / ZBH009-2019, the fire resistance of the glass is tested, and the complete fire resistance time is used as the test index, and the complete fire resistance time is 5.2-5.5h; according to the method in T / ZBH009-2019, the heat shock resistance of the glass is tested, and the maximum heat shock resistance temperature difference is used as the test index, and the heat shock resistance temperature difference is 430-460°C;
[0033] The high borosilicate glass of the present invention has relatively excellent light transmittance, and can still maintain a high light transmittance after flame impact. According to the method in GB / T2680-2021, the visible light transmittance and the total solar energy transmittance of the glass sample are detected. According to the method in T / ZBH009-2019, the glass is subjected to a fire resistance test, and the percentage of decrease in the visible light transmittance and the total solar energy transmittance, that is, the loss rate, is calculated. The visible light transmittance is 98.57-98.78%, and the visible light transmittance after flame impact is 96.82-97.10%, and the loss rate is 1.47-1.94%; the total solar energy transmittance is 99.04-99.21%, and the total solar energy transmittance after flame impact is 97.22-97.57%, and the loss rate is 1.47-1.99%;
[0034] The high borosilicate glass of the present invention has excellent chemical resistance. According to the method in GB / T34843-2017, the acid resistance and alkali resistance of the glass are tested. In the acid resistance test, the amount of sodium oxide precipitated by atomic absorption spectrometry is 17-22 μg / dm 2 , the acid resistance grade of the weight method is grade 1; the alkali resistance is grade A1;
[0035] The high borosilicate glass of the present invention has a small change in flatness after being subjected to flame impact. According to the method in T / ZBH009-2019, the initial flatness of the glass sample is tested, and its bow curvature and waveform curvature are tested respectively. According to the method in T / ZBH009-2019, the glass is subjected to a fire resistance test. After the impact is completed, the glass sample is naturally cooled to room temperature, and the bow curvature and waveform curvature of the glass sample are tested again. The initial bow curvature of the glass is 0.14-0.16%, and the bow curvature after flame impact is 0.19-0.22%. The initial waveform curvature of the glass is 0.07-0.11mm / 300mm, and the waveform curvature after flame impact is 0.14-0.20mm / 300mm. DETAILED DESCRIPTION Example 1
[0036] A flame-impact-resistant high borosilicate glass, wherein the raw materials of the glass include phosphotasysine, freeze-dried nano-cristobalite, boron oxide, iron-chromium lignin sodium sulfonate-treated aluminum oxide, sodium oxide, lithium oxide, and titanium oxide, and the mass ratio of the raw material components is 650:275:120:75:12:10:27;
[0037] The silicon dioxide content of the phosphotquartz is 99.84wt% and the particle size is 73μm;
[0038] The particle size of the titanium oxide is 34 μm.
[0039] The freeze-dried nano-cristobalite preparation method comprises lanthanum nitrate treatment and freeze-drying;
[0040] The method for the lanthanum nitrate treatment is:
[0041] The nano-scale cristobalite and the lanthanum nitrate solution are mixed evenly, and sent to a grinder, and the rotation speed of the grinder is controlled to be 1200 r / min, and the grinding time is 25 minutes. After the grinding is completed, the nano-scale cristobalite is washed with deionized water until the pH value is 6.7, and then dried to obtain the nano-scale cristobalite treated with lanthanum nitrate;
[0042] The mass ratio of the nanoscale cristobalite to the lanthanum nitrate solution is 1:7;
[0043] The nanoscale cristobalite has a silicon dioxide content of 99.85 wt%, a particle size of 140 nm, and a density of 2.44 g / cm 3 ;
[0044] The concentration of the lanthanum nitrate solution is 7.5wt%.
[0045] The freeze-drying method is:
[0046] The lanthanum nitrate treated nano-quartz was mixed with the oxalic acid solution, stirred at a speed of 120 r / min for 60 min, and after the stirring was completed, the cooling rate was controlled to be 2°C / min, and the temperature was cooled to -40°C, and then maintained for 240 min, and then the pressure was adjusted to 5 Pa for sublimation drying to obtain freeze-dried nano-quartz;
[0047] The mass ratio of the nano-cristobalite treated with lanthanum nitrate to the oxalic acid solution is 1:10;
[0048] The concentration of the oxalic acid solution is 0.5 mol / L.
[0049] The preparation method of the aluminum oxide treated with sodium ferrochrome lignin sulfonate is as follows:
[0050] The nano-alumina is mixed with deionized water, stirred to make it dispersed evenly, and an alumina dispersion is obtained. Then, sodium iron chromium lignin sulfonate is added to the alumina dispersion, the speed is controlled to be 240 r / min, and stirring is performed. During the stirring process, hydrogen peroxide is continuously added, and the adding time of hydrogen peroxide is controlled to be 10 minutes. After the addition is completed, the temperature is controlled to be 62° C., the speed is adjusted to 120 r / min, and stirring is continued for 360 minutes. After the stirring is completed, the pH is adjusted to 9.7, and the temperature and speed are maintained to continue stirring for 30 minutes. After the stirring is completed, the product is filtered, washed, and dried to obtain sodium iron chromium lignin sulfonate treated alumina;
[0051] The mass ratio of the nano-alumina, deionized water, sodium iron-chromium lignin sulfonate, and hydrogen peroxide is 15:150:2:1;
[0052] The particle size of the nano-alumina is 50 nm;
[0053] The concentration of the hydrogen peroxide is 30wt%.
[0054] The preparation method of the high borosilicate glass is:
[0055] The specified mass of phosphotyrite, freeze-dried nano-cristobalite, boron oxide, alumina treated with sodium iron-chromium lignin sulfonate, sodium oxide, lithium oxide and titanium oxide in the raw material components are mixed evenly, placed in a platinum crucible, and melted at a temperature of 1520°C. After all the components are completely melted, the temperature is raised to 1650°C to obtain glass liquid. The glass liquid is passed through a tin bath, the molding temperature in the tin bath is controlled to be 850°C, the outlet temperature of the tin bath is controlled to be 615°C, float molding is performed, and after molding, the glass is taken out of the tin bath and annealed to obtain a high borosilicate glass resistant to flame impact. Example 2
[0056] A flame-impact-resistant high borosilicate glass, wherein the raw materials of the glass include phosphotasysine, freeze-dried nano-cristobalite, boron oxide, aluminum oxide treated with sodium iron-chromium lignin sulfonate, sodium oxide, lithium oxide, and titanium oxide, and the mass ratio of the raw material components is 600:250:110:65:10:9:24;
[0057] The silicon dioxide content of the phosphotquartz is 99.84wt% and the particle size is 73μm;
[0058] The particle size of the titanium oxide is 34 μm.
[0059] The freeze-dried nano-cristobalite preparation method comprises lanthanum nitrate treatment and freeze-drying;
[0060] The method for the lanthanum nitrate treatment is:
[0061] The nano-scale cristobalite and lanthanum nitrate solution are mixed evenly, and sent to a grinder, and the rotation speed of the grinder is controlled to be 1150r / min, and the grinding time is 30min. After the grinding is completed, the nano-scale cristobalite is washed with deionized water until the pH value is 6.6, and then dried to obtain nano-scale cristobalite treated with lanthanum nitrate;
[0062] The mass ratio of the nanoscale cristobalite to the lanthanum nitrate solution is 1:6.5;
[0063] The nanoscale cristobalite has a silicon dioxide content of 99.85 wt%, a particle size of 140 nm, and a density of 2.44 g / cm 3 ;
[0064] The concentration of the lanthanum nitrate solution is 7.0 wt %.
[0065] The freeze-drying method is:
[0066] The lanthanum nitrate treated nano-quartz was mixed with the oxalic acid solution, stirred at a speed of 100 r / min for 80 min, and after the stirring was completed, the temperature was cooled at a rate of 1.5°C / min, and after cooling to -35°C, it was kept for 260 min, and then the pressure was adjusted to 3 Pa for sublimation drying to obtain freeze-dried nano-quartz;
[0067] The mass ratio of the nano-cristobalite treated with lanthanum nitrate to the oxalic acid solution is 1:7.5;
[0068] The concentration of the oxalic acid solution is 0.75 mol / L.
[0069] The preparation method of the aluminum oxide treated with sodium ferrochrome lignin sulfonate is as follows:
[0070] The nano-alumina is mixed with deionized water, stirred to make it dispersed evenly, and an alumina dispersion is obtained, and then sodium iron chromium lignin sulfonate is added to the alumina dispersion, the speed is controlled to be 210r / min, and stirring is performed, and hydrogen peroxide is continuously added during the stirring process, and the adding time of hydrogen peroxide is controlled to be 15min. After the addition is completed, the temperature is controlled to be 60°C, the speed is adjusted to be 130r / min, and stirring is continued for 330min. After the stirring is completed, the pH is adjusted to 9.5, and the temperature and speed are maintained to continue stirring for 35min. After the stirring is completed, the product is filtered, washed, and dried to obtain sodium iron chromium lignin sulfonate treated alumina;
[0071] The mass ratio of the nano-alumina, deionized water, sodium iron-chromium lignin sulfonate, and hydrogen peroxide is 10:100:1.8:0.9;
[0072] The particle size of the nano-alumina is 50 nm;
[0073] The concentration of the hydrogen peroxide is 35wt%.
[0074] The preparation method of the high borosilicate glass is:
[0075] The specified mass of phosphotyrite, freeze-dried nano-cristobalite, boron oxide, alumina treated with sodium iron-chromium lignin sulfonate, sodium oxide, lithium oxide and titanium oxide in the raw material components are mixed evenly, placed in a platinum crucible, and melted at a temperature of 1510°C. After all the components are completely melted, the temperature is raised to 1620°C to obtain glass liquid. The glass liquid is passed through a tin bath, the molding temperature in the tin bath is controlled to be 825°C, the outlet temperature of the tin bath is controlled to be 610°C, float molding is performed, the molding is taken out of the tin bath, and annealing is performed to obtain a high borosilicate glass resistant to flame impact. Example 3
[0076] A flame-impact-resistant high borosilicate glass, wherein the raw materials of the glass include phosphotasysine, freeze-dried nano-cristobalite, boron oxide, alumina treated with sodium iron-chromium lignin sulfonate, sodium oxide, lithium oxide, and titanium oxide, and the mass ratio of the raw material components is 700:300:130:85:14:11:30;
[0077] The silicon dioxide content of the phosphotquartz is 99.84wt% and the particle size is 73μm;
[0078] The particle size of the titanium oxide is 34 μm.
[0079] The freeze-dried nano-cristobalite preparation method comprises lanthanum nitrate treatment and freeze-drying;
[0080] The method for the lanthanum nitrate treatment is:
[0081] The nano-scale cristobalite and the lanthanum nitrate solution are mixed evenly, and sent to a grinder, and the rotation speed of the grinder is controlled to be 1250r / min, and the grinding time is 20min. After the grinding is completed, the nano-scale cristobalite is washed with deionized water until the pH value is 6.8, and then dried to obtain the nano-scale cristobalite treated with lanthanum nitrate;
[0082] The mass ratio of the nanoscale cristobalite to the lanthanum nitrate solution is 1:75;
[0083] The nanoscale cristobalite has a silicon dioxide content of 99.85 wt%, a particle size of 140 nm, and a density of 2.44 g / cm 3 ;
[0084] The concentration of the lanthanum nitrate solution is 8.0 wt %.
[0085] The freeze-drying method is:
[0086] The lanthanum nitrate treated nano-quartz was mixed with the oxalic acid solution, stirred at a speed of 150 r / min for 50 min, and after the stirring was completed, the temperature was cooled at a rate of 2.5°C / min, and after cooling to -45°C, it was kept for 230 min, and then the pressure was adjusted to 6 Pa for sublimation drying to obtain freeze-dried nano-quartz;
[0087] The mass ratio of the nano-cristobalite treated with lanthanum nitrate to the oxalic acid solution is 1:12.5;
[0088] The concentration of the oxalic acid solution is 0.4 mol / L.
[0089] The preparation method of the aluminum oxide treated with sodium ferrochrome lignin sulfonate is as follows:
[0090] The nano-alumina was mixed with deionized water, and stirred to make it dispersed evenly to obtain an alumina dispersion, and then sodium iron-chromium lignin sulfonate was added to the alumina dispersion, and the speed was controlled to be 260 r / min, and stirring was performed. During the stirring process, hydrogen peroxide was continuously added, and the adding time of hydrogen peroxide was controlled to be 8 minutes. After the addition was completed, the temperature was controlled to be 65° C., the speed was adjusted to 90 r / min, and stirring was continued for 400 minutes. After the stirring was completed, the pH was adjusted to 9.9, and the temperature and speed were maintained to continue stirring for 25 minutes. After the stirring was completed, the product was filtered, washed, and dried to obtain sodium iron-chromium lignin sulfonate treated alumina;
[0091] The mass ratio of the nano-alumina, deionized water, sodium iron-chromium lignin sulfonate, and hydrogen peroxide is 20:200:2.2:1.1;
[0092] The particle size of the nano-alumina is 50 nm;
[0093] The concentration of the hydrogen peroxide is 25wt%.
[0094] The preparation method of the high borosilicate glass is:
[0095] The specified mass of phosphotyrite, freeze-dried nano-cristobalite, boron oxide, alumina treated with sodium iron-chromium lignin sulfonate, sodium oxide, lithium oxide and titanium oxide in the raw material components are mixed evenly, placed in a platinum crucible, and melted at a temperature of 1550°C. After all the components are completely melted, the temperature is raised to 1670°C to obtain glass liquid. The glass liquid is passed through a tin bath, the molding temperature in the tin bath is controlled to be 875°C, the outlet temperature of the tin bath is controlled to be 620°C, float molding is performed, the molding is taken out of the tin bath, and annealing is performed to obtain a high borosilicate glass resistant to flame impact.
[0096] Comparative Example 1
[0097] The difference from Example 1 is that the lanthanum nitrate treatment step in the freeze-drying method for preparing nano-cristobalite is omitted, and the untreated nano-scale cristobalite is directly subjected to the freeze-drying step, and is used as a raw material component of high borosilicate glass while keeping the dosage unchanged. The remaining steps are the same to prepare the glass.
[0098] Comparative Example 2
[0099] The difference from Example 1 is that the freeze-drying step in the preparation method of freeze-drying nano-cristobalite is omitted, and the lanthanum nitrate-treated nano-cristobalite obtained in the lanthanum nitrate treatment step is used as a raw material component of high borosilicate glass. The glass is prepared while the remaining steps remain unchanged while the dosage remains unchanged.
[0100] Comparative Example 3
[0101] Different from Example 1, the step of treating alumina with sodium iron chromium lignin sulfonate is omitted, and untreated nano alumina is used as the raw material component of high borosilicate glass. The glass is prepared while the dosage remains unchanged and the other steps remain unchanged.
[0102] Test Example 1 Glass Strength Test
[0103] The bending strength of the high borosilicate glass of Examples 1-3 and Comparative Examples 1-3 was tested according to the method in T / ZBH009-2019; the elastic modulus and shear modulus of the high borosilicate glass were tested according to the method in GB / T37780-2019; the shotgun bag impact performance of the glass was tested according to the method in T / ZBH009-2019, with the highest height at which the shotgun bag dropped the sample without being damaged as the test index; the surface stress of the high borosilicate glass was tested according to the method in GB15763.2-2005, and the results are shown in Table 1.
[0104] Table 1
[0105]
[0106] In Example 1-3, nano-scale cristobalite is subjected to two-step special treatment, and nano-scale alumina is treated with sodium iron chromium lignin sulfonate, and both are used as raw material components of glass. The synergistic effect of the two can improve the mechanical properties of the glass.
[0107] Comparative Example 1: In the preparation method of freeze-drying nano-cristobalite, the lanthanum nitrate treatment step is omitted, and the untreated nano-scale cristobalite is directly freeze-dried and used as a raw material component of high borosilicate glass, which will lead to a decrease in the mechanical properties of the glass, especially the bending strength. In addition, the elastic modulus, shear modulus, impact resistance, and surface stress all decrease to a certain extent.
[0108] Comparative Example 2: Omitting the freeze-drying step in the preparation method of freeze-dried nano-cristobalite and using the lanthanum nitrate-treated nano-cristobalite obtained in the lanthanum nitrate treatment step as a raw material component of high borosilicate glass will lead to a decrease in the mechanical properties of the glass, especially the decrease in elastic modulus and impact resistance. In addition, the bending strength, shear modulus, and surface stress all decrease to a certain extent.
[0109] Comparative Example 3 omits the step of treating alumina with sodium iron-chromium-lignin sulfonate, and uses untreated nano-alumina as a raw material component of high borosilicate glass, which will lead to a decrease in the mechanical properties of the glass, especially the shear modulus and surface stress. In addition, the bending strength, elastic modulus, shear modulus, and impact resistance all decrease to a certain extent.
[0110] Test Example 2 Glass fire resistance and heat resistance test
[0111] The high borosilicate glass of Examples 1-3 and Comparative Examples 1-3 was tested for fire resistance according to the method in T / ZBH009-2019, with the complete fire resistance time as the test index; the thermal shock resistance of the glass was tested according to the method in T / ZBH009-2019, with the maximum thermal shock resistance temperature difference as the test index. The results are shown in Table 2.
[0112] Table 2
[0113]
[0114] Example 1-3: Nano-scale cristobalite is subjected to two-step special treatment, and nano-scale alumina is treated with sodium iron chromium lignin sulfonate, and both are used as raw material components of glass. The synergistic effect of the two can improve the fire resistance and heat resistance of the glass.
[0115] Comparative Example 1: In the preparation method of freeze-drying nano-cristobalite, the lanthanum nitrate treatment step is omitted, and the untreated nano-scale cristobalite is directly freeze-dried and used as a raw material component of high borosilicate glass, which will lead to a decrease in the fire resistance and heat resistance of the glass, and the fire resistance integrity time and the heat shock resistance temperature difference will decrease to a certain extent;
[0116] Comparative Example 2: The freeze-drying step in the preparation method of freeze-drying nano-cristobalite is omitted, and the lanthanum nitrate-treated nano-cristobalite obtained in the lanthanum nitrate treatment step is used as a raw material component of high borosilicate glass, which will lead to a decrease in the fire resistance and heat resistance of the glass, especially a serious decrease in the fire resistance integrity time, and a certain degree of decrease in the heat shock resistance temperature difference;
[0117] Comparative Example 3 omits the step of treating alumina with sodium iron-chromium lignin sulfonate, and uses untreated nano-alumina as a raw material component of high borosilicate glass, which will lead to a decrease in the fire resistance and heat resistance of the glass, especially a serious decrease in the temperature difference of heat shock resistance, and a certain degree of decrease in the fire resistance integrity time.
[0118] Test Example 3: Test of glass optical properties and changes in optical properties after flame impact
[0119] The high borosilicate glass of Examples 1-3 and Comparative Examples 1-3 was tested for visible light transmittance and total solar energy transmittance of the glass samples according to the method in GB / T2680-2021, and then the glasses of Examples 1-3 and Comparative Examples 1-3 were subjected to a fire resistance test according to the method in T / ZBH009-2019, and the flame impact time was set to 3h. After the impact was completed, the glass samples were naturally cooled to room temperature, and then the glass surface was cleaned to remove the influence of surface smoke and dust, and the visible light transmittance and total solar energy transmittance of the glass samples were tested again, and the percentage of decrease in visible light transmittance and total solar energy transmittance, i.e., the loss rate, was calculated. The results are shown in Table 3.
[0120] Table 3
[0121]
[0122] In Example 1-3, nano-scale cristobalite is subjected to two-step special treatment, and nano-scale alumina is treated with sodium iron chromium lignin sulfonate, and both are used as raw material components of glass. The synergistic effect of the two can reduce the impact of flame impact on the transparency of the glass;
[0123] Comparative Example 1: In the preparation method of freeze-drying nano-cristobalite, the lanthanum nitrate treatment step is omitted, and the untreated nano-scale cristobalite is directly freeze-dried and used as a raw material component of high borosilicate glass, which will cause the flame shock to have a greater effect on the transparency of the glass, and both the visible light transmittance and the total solar energy transmittance will suffer a greater degree of loss;
[0124] Comparative Example 2: The freeze-drying step in the preparation method of freeze-drying nano-cristobalite is omitted, and the lanthanum nitrate-treated nano-cristobalite obtained in the lanthanum nitrate treatment step is used as a raw material component of high borosilicate glass, which will cause the effect of flame impact on the transparency of the glass to become greater, especially the loss rate of visible light transmittance, which decreases seriously, and the total solar transmittance also suffers a large degree of loss;
[0125] Comparative Example 3 omits the step of treating alumina with sodium iron-chromium lignin sulfonate, and uses untreated nano-alumina as a raw material component of high borosilicate glass, which will cause the effect of flame impact on the transparency of the glass to become greater, especially the loss rate of total solar energy transmittance, which decreases seriously. In addition, the visible light transmittance is also lost to a large extent.
[0126] Test Example 4 Glass Chemical Resistance Test
[0127] The high borosilicate glass of Examples 1-3 and Comparative Examples 1-3 was tested for acid resistance and alkali resistance according to the method in GB / T34843-2017. In the acid resistance, the atomic absorption spectrometry was used to measure the amount of sodium oxide precipitation in μg / dm 2 , less than 100μg / dm 2 The results are shown in Table 4.
[0128] Table 4
[0129]
[0130] In Example 1-3, nano-scale cristobalite is subjected to two-step special treatment, and nano-scale alumina is treated with sodium iron chromium lignin sulfonate, and both are used as raw material components of glass. The synergistic effect of the two can improve the chemical resistance of the glass;
[0131] Comparative Example 1: The lanthanum nitrate treatment step in the preparation method of freeze-drying nano-cristobalite is omitted, and the untreated nano-scale cristobalite is directly freeze-dried and used as a raw material component of high borosilicate glass, which will lead to a decrease in the chemical resistance of the glass. In the acid resistance test, although the weight method can reach level 1, in the atomic absorption spectrometry method, the amount of sodium oxide precipitated is large, and the alkali resistance is reduced to a certain extent;
[0132] Comparative Example 2: The freeze-drying step in the preparation method of freeze-drying nano-cristobalite is omitted, and the lanthanum nitrate-treated nano-cristobalite obtained in the lanthanum nitrate treatment step is used as a raw material component of high borosilicate glass, which will lead to a decrease in the chemical resistance of the glass. In the acid resistance test, although the weight method can reach level 1, in the atomic absorption spectrometry method, the amount of sodium oxide precipitated is large, and the alkali resistance is reduced to a certain extent;
[0133] Comparative Example 3 omits the step of treating alumina with sodium iron chromium lignin sulfonate, and uses untreated nano alumina as a raw material component of high borosilicate glass, which will lead to a decrease in the chemical resistance of the glass, especially the decrease in acid resistance. In the acid resistance test, although the weight method can reach level 1, the amount of sodium oxide precipitated is relatively large in the atomic absorption spectrometry method.
[0134] Test Example 5: Flatness change test of glass after flame impact
[0135] The high borosilicate glasses of Examples 1-3 and Comparative Examples 1-3 were tested for initial flatness, bow curvature and waveform curvature according to the method in T / ZBH009-2019, and the records were made. Then, the glasses of Examples 1-3 and Comparative Examples 1-3 were subjected to fire resistance tests according to the method in T / ZBH009-2019, and the flame impact time was set to 3h. After the impact was completed, the glass samples were naturally cooled to room temperature, and the bow curvature and waveform curvature of the glass samples were tested again. The results are shown in Table 5.
[0136] Table 5
[0137]
[0138] In Example 1-3, nano-scale cristobalite is subjected to two-step special treatment, and nano-scale alumina is treated with sodium iron chromium lignin sulfonate, and both are used as raw material components of glass. The synergistic effect of the two can reduce the influence of flame impact on the curvature of the glass;
[0139] Comparative Example 1: In the preparation method of freeze-drying nano-cristobalite, the lanthanum nitrate treatment step is omitted, and the untreated nano-scale cristobalite is directly freeze-dried and used as a raw material component of high borosilicate glass, which will cause the effect of flame impact on the curvature of the glass to become greater, and both the bow curvature and the wave curvature will decrease to a certain extent;
[0140] Comparative Example 2: The freeze-drying step in the preparation method of freeze-drying nano-cristobalite is omitted, and the lanthanum nitrate-treated nano-cristobalite obtained in the lanthanum nitrate treatment step is used as a raw material component of high borosilicate glass, which will cause the effect of flame impact on the curvature of the glass to become greater, and the decrease of the bow curvature and the wave curvature is more serious;
[0141] Comparative Example 3 omits the step of treating alumina with sodium iron-chromium-lignin sulfonate, and uses untreated nano-alumina as a raw material component of high borosilicate glass, which will cause the effect of flame impact on the curvature of the glass to become greater, and both the bow curvature and the wave curvature will decrease to a certain extent.
Claims
1. A flame-impact resistant borosilicate glass, characterized in that: The raw materials of the glass include phosphotris, freeze-dried nano-cristobalite, boron oxide, aluminum oxide treated with sodium iron-chromium lignin sulfonate, sodium oxide, lithium oxide, and titanium oxide, and the mass ratio of the raw material components is 600-700:250-300:110-130:65-85:10-14:9-11:24-30; The freeze-dried nano-cristobalite preparation method comprises lanthanum nitrate treatment and freeze-drying; The method for treating with lanthanum nitrate is as follows: nano-scale cristobalite is uniformly mixed with a lanthanum nitrate solution, and then fed into a grinder, the rotation speed of the grinder is controlled to be 1150-1250 r / min, and grinding is performed for 20-30 min. After grinding, the mixture is washed with deionized water until the pH value is 6.6-6.8, and then dried to obtain nano-cristobalite treated with lanthanum nitrate; The mass ratio of the nanoscale cristobalite to the lanthanum nitrate solution is 1:6.5-7.5; The concentration of the lanthanum nitrate solution is 7.0-8.0wt%; The freeze-drying method comprises: uniformly mixing the nano-cristobalite treated with lanthanum nitrate and the oxalic acid solution, stirring at a speed of 100-150 r / min for 50-80 min, and after the stirring is completed, controlling the cooling rate to be 1.5-2.5° C. / min, cooling to -35 to -45° C., maintaining the temperature for 230-260 min, and then adjusting the pressure to 3-6 Pa for sublimation drying to obtain the freeze-dried nano-cristobalite; The mass ratio of the nano-cristobalite treated with lanthanum nitrate to the oxalic acid solution is 1:7.5-12.5; The concentration of the oxalic acid solution is 0.4-0.75 mol / L; The preparation method of the sodium iron chromium lignin sulfonate treated aluminum oxide comprises the following steps: mixing nano aluminum oxide with deionized water, stirring to make the mixture dispersed evenly, obtaining an aluminum oxide dispersion, then adding the sodium iron chromium lignin sulfonate to the aluminum oxide dispersion, controlling the speed to be 210-260 r / min, stirring, continuously adding hydrogen peroxide during stirring, controlling the adding time of the hydrogen peroxide to be 8-15 min, after the addition is completed, controlling the temperature to be 60-65° C., adjusting the speed to be 90-130 r / min, continuing stirring, and stirring for 330-400 min, after the stirring is completed, adjusting the pH to be 9.5-9.9, maintaining the temperature and speed and continuing stirring for 25-35 min, and after the stirring is completed, filtering, washing, and drying the product to obtain the sodium iron chromium lignin sulfonate treated aluminum oxide; The mass ratio of the nano-alumina, deionized water, sodium iron-chromium lignin sulfonate, and hydrogen peroxide is 10-20:100-200:1.8-2.2:0.9-1.1; The concentration of the hydrogen peroxide is 25-35wt%.
2. The flame-impact resistant borosilicate glass according to claim 1, characterized in that: In the raw materials of the glass, the silicon dioxide content of phosphotidite is 99.84wt% and the particle size is 73μm.
3. The flame-impact resistant borosilicate glass according to claim 1, characterized in that: Among the raw materials of the glass, the particle size of titanium oxide is 34 μm.
4. The flame-impact resistant borosilicate glass according to claim 1, characterized in that: In the lanthanum nitrate treatment step, the silicon dioxide content of the nanoscale cristobalite is 99.85wt%, the particle size is 140nm, and the density is 2.44g / cm 3 .
5. The flame-impact resistant borosilicate glass according to claim 1, characterized in that: In the method for preparing alumina treated with sodium ferrochrome lignin sulfonate, the particle size of nano alumina is 50 nm.
6. The method for preparing a flame-impact resistant borosilicate glass according to claim 1, characterized in that: The preparation method comprises the following steps: uniformly mixing phosphotris, freeze-dried nano-cristobalite, boron oxide, alumina treated with sodium iron-chromium lignin sulfonate, sodium oxide, lithium oxide and titanium oxide of a specified mass among the raw material components, placing the mixture in a platinum crucible, controlling the temperature to be 1510-1550° C., melting the mixture, raising the temperature to 1620-1670° C. after all the components are completely melted, passing the mixture through a tin bath, controlling the molding temperature in the tin bath to be 825-875° C., controlling the outlet temperature of the tin bath to be 610-620° C., performing float molding, exiting the tin bath after molding, and annealing the mixture to obtain a high borosilicate glass resistant to flame impact.
Citation Information
Patent Citations
High-strength high-temperature-resistance high borosilicate glass
CN108455847A
Preparation method of high heat resistance chemical stable high borosilicate glass
CN109133618A